PENGARUH KEJENUHAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 CAMPALAGIAN - Usman, Husnaeni; M. Ridwan Tikollah; Fajriani Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of learning saturation on student learning achievement in class XI IPS in Economics Subject at SMA Negeri 1 Campalagian. The variables in the study are learning saturation as the independent variable (X) and learning achievement as the dependent variable (Y). The population in this study were 110 students of class XI IPS at SMA Negeri 1 Campalagian. The number of samples was 52 students who were carried out using random sampling techniques. The data collection techniques used were questionnaires and documentation. The collected data were analyzed using statistical analysis, instrument testing, and hypothesis testing using SPSS Version 25. Based on the results of the analysis obtained, it is known that the simple linear regression equation model Y = 95.412-0.277 X which means that for every additional value of learning saturation, learning achievement decreases by 0.277. From the value of the coefficient of determination analysis (r2) obtained the value of r2 = 0.227 which shows that learning saturation has a contribution of 22.7% to the learning achievement of class XI IPS students in the subject of economics at SMA Negeri 1 Campalagian. and the remaining 77.3% is influenced by other factors. Meanwhile, from the results of the t-test analysis obtained a significant value of 0.000 <0.05 which means that the learning saturation variable has a negative and significant effect on the learning achievement of class XI IPS students in the subject of economics at SMA Negeri 1 Campalagian, thus the hypothesis "is accepted".